Functional Performance in Children with Down Syndrome: Correlations between Social Support and the Quality of Life of Caregivers - , Luciana Krauss Rezende; , Fátima Aparecida Caromano; , Sueli Galego de Carvalho; , Selma Petra Chaves Sá; , Luiz Fernando Barca; , Wiliam César Alves Machado; , Silvana Maria Blascovi de Assis (Archives of Current Research International, 2018)
Children with Down syndrome (DS) have neuro-sensorimotor disorders that limit their functionality and social participation. The aim of the study was to investigate the relationship between functional performance of children with DS and the perception of social support, quality of life and socioeconomic status of their caregivers. To develop the proposed objectives, we opted for a clinical study of character, quantitative analysis, exploratory and descriptive cross-sectional. Fifty caregivers of both genders, caregivers of children with DS, aged between six months and seven and a half years, were divided into two subgroups homogeneous for ages 6 months to 4 years (n = 24) and over 4 years to 7 years (n = 26), regulars of specialized institutions. The instruments used were WHOQOL Bref, social support scale, Inventory Ordered evaluation. The results obtained from the application inventory Pedi were different for children of different age groups. For children under 4 years there is a significant correlation between the indexes Cuidador- Assistance Self-care and quality of life, negative correlation that can be considered moderate and among the indices caregiver assistance - Social Function and Social Support, positive correlation that can be considered moderate. For children older than four years, there is no significant correlation between the indicators of Pedi and indicators Social Support, Quality of Life and Economic Partner Level. We conclude that there is relationship between functional performance, perceived social support, quality of life and socio-economic status of their caregivers in SD with the group of children under 4 years old. Work to identify ways of intervention for this group should be the subject of future investigations mainly favoring social support for families, assuming that social support integrates the policies on inclusive education.